Frictional capital reallocation I: Ex ante heterogeneity - Randall D. Wright; Sylvia Xiaolin Xiao; Yu Zhu (Bank of Canada, 2019)
This paper studies dynamic general equilibrium models where firms trade capital in frictional markets. Gains from trade arise due to ex ante heterogeneity: some firms are better at investment, so they build capital in the primary market; others acquire it in the secondary market. Cases are considered with random search and bargaining, or directed search and posting. For each, we provide results on existence, uniqueness, efficiency and comparative statics. Monetary and fiscal policy are discussed at length. We also discuss how productivity dispersion can be countercyclical while capital reallocation and its price are procyclical.
Keywords: E22; E44; 330; Monetary policy